Kajian Struktur Serat dan Porositas Masker Udara - Handika Dany Rahmayanti; Rahmawati Rahmawati; Euis Sustini; Mikrajuddin Abdullah (Jurnal Fisika, 2018)
There are 6 brands of air masks on the market that are Evo med, Nexcare carbon, Nexcare daily, Indomaret, Borma and Evo club. All masks on the market have 3 layers. Based on the results of microscopy testing showed that the fiber diameter image of all mask brands in layer 2 is smaller than layer 1 and 3. Generally, all brands of masks show a uniform fiber size distribution. From the surface porosity measurements, Borma masks have a larger porosity than other masks in layers 1, 2 and 3 ie 60.64%, respectively; 42.95% and 63.58%. The results show that the difference in mask price in the market does not show the quality standards of different mask filters. Furthermore, the results of this study may contribute to the development of research on masks.